Activation and Detoxification Enzymes Functions and Implications - Chen, Chang-Hwei (Springer New York : Imprint: Springer, 2012)
There are many advances that have been made in the past decades towards the understanding of functions and implications of activation enzymes and detoxification enzymes. An organized, concise overview is needed for the readers who are initially exposed to this important subject, particularly for students and researchers in the areas of biomedical sciences, biochemistry, nutrition, pharmacology and chemistry. This book is intended to serve this purpose as an introduction to the subject. Furthermore, major topics in the book, excluding catalytic reactions and structural properties, may have interest to other readers who have knowledge of basic sciences and understanding enzyme related information. The book discusses subjects associated with foreign compound metabolizing enzymes with emphasis on biochemical aspects, including lipophilic foreign compounds, phase I and phase II enzymes, catalytic properties, reactive intermediates, biomedical and biochemical effects, genetic polymorphisms, enzyme inducibility, enzyme modulation for health benefits, dietary related enzyme modulators, and structural characteristics of enzyme inducers. .